Pendampingan Inventarisasi dan Penomoran Aset Pondok Pesantren Al Mubarokah - Kalsum, Umi; Safitri, Rika Henda; Mukhtaruddin, Mukhtaruddin; Fuadah, Luk Luk; Wahyudi, Tertiarto; Atiyatna, Dirta Pratama; Novelia, Riska; Rahmawati, Rahmawati; Jamilah, Wardatul; Febriani, Fenti; Abdillah, Muhammad (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The purpose of community service activities carried out at Pondok Pesantren Al-Mubarokah, Babat Supat Village, Musi Banyuasin Regency is to increase participants' understanding of asset management, including identification, classification, valuation, recording, inventorying and numbering assets. The lack of good asset inventory records and numbering is the reason for this activity, with the hope that in the future assets can be inventoried properly and be able to be traced. The methods used included lectures, tutorials, and discussions, involving boarding school leaders and school staff, and accompanied by students. Evaluation was carried out through questionnaires to measure participants' understanding. This activity was held on 28 September 2024, attended by 30 participants, and ended with a discussion and lunch together. A follow-up evaluation on 28 October 2024 showed the enthusiasm of the participants and emphasised the importance of asset inventory and asset numbering. The results of this activity by providing practical examples of asset inventory bookkeeping and asset numbering to be implemented at Pesantren Al Mubarokah, besides that this activity also provides practical experience for the academic elements of the pesantren, especially the school staff at Pesantren Al Mubarokah.